2012
DOI: 10.1177/0892705712455036
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hansen solubility parameters to predict dispersion and strain transfer of functionalized single-walled carbon nanotubes in poly(vinylidene fluoride) composites

Abstract: In this article, Hansen solubility parameters (HSP) have been used to evaluate the dispersion state and interfacial strain transfer ability of purified, nitric acid-functionalized and octadecylamine-functionalized single-walled carbon nanotubes (SWNTs) as the reinforcing materials in a poly(vinylidene fluoride) (PVDF) matrix. Composites were prepared by solution blending of PVDF and SWNTs and injection molding. The observations of the dispersion were obtained by dynamic light scattering and light optical micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…The same hydrogen bonding can be formed between functional groups in MCNT and C–F of FE. Ma and Larsen 40 also reported that nitric acid–treated single wall nanotubes compared to untreated MWNT have better physical surface affinities with PVDF. The same compatibility can be mentioned here between ACNT and FE compared to CNT and FE.…”
Section: Resultsmentioning
confidence: 96%
“…The same hydrogen bonding can be formed between functional groups in MCNT and C–F of FE. Ma and Larsen 40 also reported that nitric acid–treated single wall nanotubes compared to untreated MWNT have better physical surface affinities with PVDF. The same compatibility can be mentioned here between ACNT and FE compared to CNT and FE.…”
Section: Resultsmentioning
confidence: 96%
“…The same hydrogen bonding can be formed between functional groups in MCNT and C-F of FE. Ma and Larsen [26] also reported that nitric acid treated single wall nanotubes (SWNT) compared to untreated MWNT have better physical surface affinities with PVDF. The same compatibility can be mentioned here between MCNT and FE compared to CNT and FE.…”
Section: Verifying Thermal Stability In Fe Compositesmentioning
confidence: 99%
“…Poly(vinylidene fluoride) (PVDF) is a semicrystalline thermoplastic polymer having fine thermal stability, chemical resistance, mechanical strength, elasticity, and piezoelectric and pyroelectric characteristics. 1,2 Because of outstanding properties, PVDF own wide range of applications in biomedical, electronics, supercapacitors, actuators, batteries, and so on. PVDF exits in five different crystalline forms as a, b, d, g, and e-phase.…”
Section: Introductionmentioning
confidence: 99%